Melody In Color: Examining The Mood Induction Effect of Indian Classical Music of Varying Tempos and Valence on Color Preference - Nigam, Sargun (My University, 2024)
This study explored a relationship between mood modulated by Indian ragas of varying tempos and valence over color preference. Indian Ragas (positive & negative) were used for slow, neutral and fast tempos to induce mood change in the participants. A mixed method approach was adopted. First study, which was a control condition (N=60), and the second study was taken as an experimental condition (N=120). Warm and cool colors represented color preference of the participants. Varied tempos were expected to bring a change in mood of the participants which in turn was further expected to associate with color preference. As a result emotional effects were significantly different for positive and negative ragas of varying tempos. Emotional effects were observed in the form of a mood change for some tempos and not for the others. Participants chose more warm colors for positive music of varying tempos, or for music that sounded more pleasant to them; while others chose more cool colors for ragas that were negative or for Ragas that sounded less pleasant. In conclusion, it was found that a manipulation in tempo does affect mood change and color preference.
Keywords: Mood Induction; Valence; Color preference; Indian Ragas; Music tempo variation.